Effect of Immersion Time in Sweet Orange and Tangerine Peel Juice on Teeth Whitening (In Vitro Study) - Puspitaningrum, Putri Febiana; Hapsari, Rebriarina; Vidyahayati, Indah Lestari (Journal of Indonesian Dental Association, 2024)
Introduction: Tooth discoloration is an aesthetic problem that greatly affects appearance. The use of chemicals to treat tooth discoloration requires high cost and can cause tooth hipersensitivity. Sweet orange peel and tangerine peel contain organic acids and d-limonene which have the potential to be alternative bleaching agents. Objective: To determine the effect of immersion time in sweet orange peel juice (Citrus sinensis (L.) Osbeck) and tangerine peel juice (Citrus reticulata Blanco) on teeth whitening. Methods: This research was an experimental in vitro study using 30 post-extraction maxillary first premolars divided into 3 groups. Group 1 was soaked in sweet orange peel juice, group 2 was soaked in tangerine peel juice, and group 3 (negative control) was soaked in distilled water. Samples were soaked in coffee solution for 7 days and then soaked according to groups for 1 hour, 3 hours, and 5 hours. Color changes were observed with blinding method using the VITAPAN classical shade guide. Data were analyzed using Wilcoxon Sign Rank Test and Kruskal Wallis Test. Results: Sweet orange peel juice, tangerine peel juice, and distilled water showed significant differences in the observed values ​​(p<0.05) after 1 hour, 3 hours, and 5 hours of immersion. The biggest difference on the observed value was obtained after 5 hours of immersion in sweet orange peel juice and tangerine peel juice. Based on the Kruskal Wallis test and the Post Hoc Test, there are no significant differences on the average value of tooth color observations (p>0.05) between sweet orange peel juice and tangerine peel juice after 1 hour, 3 hours, and 5 hours of immersion. Conclusion: The longer the immersion time in sweet orange peel juice and tangerine peel juice, the greater the effect of teeth whitening.